Gorod Zero - Shakhnazarov, Karen (Soviet Union : Mosfilm, 1988)
An engineer in charge of the production line of a factory in Moscow is sent to a small town to try to specify the distributor the new dimensions of a mechanic part they need. But in this town everybody seems to be crazy: a secretary works naked, a group of people take the engineer as a rock & roll player, and, in addition, he becomes a witness to a suicide, becoming trapped inside the town. What we see is more than just an absurd story. Strange situations dot not merely describe an awkward way of life, they portray an end of the Soviet life as such. Overall "Gorod Zero" became a prophecy. The one from which it was nowhere to "run".
Keywords: Fiction films